Gender differences of athletes in different classification groups of sports and sport disciplines - Тарасевич, Елена Анатольевна (Slobozhanskyi Herald of Science and Sport, 2016)
Tarasevych O. Purpose: to identify the percentage of masculine, androgynous and feminine figures in different classification groups, sports and sports disciplines, depending on the sport qualification. Material & Methods: the study was conducted on the basis of the Kharkiv State Academy of Physical Culture among students – representatives of different sports that have different athletic skills using analysis and compilation of scientific and methodical literature, survey, testing the procedure S. Bam "Masculinity / femininity "Processing and statistical data. Results: based on the testing method established S. Bam percentage masculine, androgynous and feminine personalities among athletes and athletes in various sports classification groups depending on their athletic skills. Conclusions: among sportsmen and women in a variety of classification groups of sports is not revealed feminine personalities; masculine identity, among both men and women predominate in sports; androgyny attitude towards men and women are different.